2018
DOI: 10.1016/j.acvd.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation: Neurogenic or myogenic?

Abstract: A 55-year-old hypertensive patient presents atrial fibrillation after vasovagal syncope. Non-invasive cardiac workup is normal. Without antiarrhythmic therapy, the patient has no recurrence for the next 3years, then presents with a stroke. Echocardiography eventually reveals left atrial dilation. This sequence of events illustrates the well-known links between age, arterial hypertension, atrial fibrillation, atrial neuromyopathy and stroke. A frequently neglected common denominator in this equation is impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 94 publications
1
27
1
Order By: Relevance
“…In atherosclerosis, concepts have moved from a purely lipid-related, to a more complex, lipid-inflammatory pathophysiology [ 45 ]. In atrial fibrillation, concepts have moved from a purely electrical disease to a more tangled combination of electrical, structural, autonomic, and molecular underlying changes [ 46 , 47 , 48 ]. In AMI, for years, biomarkers have been focused on the concept of myocardial necrosis.…”
Section: Newer Biomarkers For Laboratory Diagnosis Of Acute Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In atherosclerosis, concepts have moved from a purely lipid-related, to a more complex, lipid-inflammatory pathophysiology [ 45 ]. In atrial fibrillation, concepts have moved from a purely electrical disease to a more tangled combination of electrical, structural, autonomic, and molecular underlying changes [ 46 , 47 , 48 ]. In AMI, for years, biomarkers have been focused on the concept of myocardial necrosis.…”
Section: Newer Biomarkers For Laboratory Diagnosis Of Acute Myocardial Infarctionmentioning
confidence: 99%
“…Myocardial inflammation is a critical process occurring in the setting of AMI that has been related to a variety of deleterious consequences, including electrical instability and increased risk of cardiac arrhythmias, autonomic dysfunction, and fibrosis development [ 48 , 62 , 63 , 64 ]. A wide variety of pro-inflammatory cytokines have been shown to increase in the setting of AMI and to predict prognosis in this population.…”
Section: Newer Biomarkers For Laboratory Diagnosis Of Acute Myocardial Infarctionmentioning
confidence: 99%
“…A few studies have suggested that autonomic imbalance is closely associated with AF, and the autonomic nervous system could be regulated by the renin–angiotensin–aldosterone system (RAAS). 2 , 3 Atrial ionic and structural remodeling is the substrate and mechanism for the process of AF. 4 Therefore, suppression of atrial remodeling may be a novel treatment for AF.…”
Section: Introductionmentioning
confidence: 99%
“…suggests that the beneficial effects of ivabradine could extend to other settings associated with increased sympathetic activity, in which the ivabradine-induced increase in vagal modulation could reduce myocardial oxygen demand and ischemia, diminish sympathetic stimulation and adrenoreceptor-mediated cytotoxicity, apoptosis, and hypertrophy, and reduce the likelihood of ventricular tachyarrhythmias and sudden death (Böhm et al, 2015). On the other hand, vagal hyperactivity has been shown to promote ectopic activity, reentry, and atrial fibrillation via multiple mechanisms (Scridon et al, 2018). Given the highly proarrhythmic effects of vagal activation at the atrial level, the increase in vagal modulation induced by ivabradine demonstrated in the present study could provide an explanation for the increased risk of atrial fibrillation associated with ivabradine use in clinical trials (Martin et al, 2014;Cammarano et al, 2016).…”
Section: Discussionmentioning
confidence: 99%